How do multinationals report their economic, social, and environmental impacts? Evidence from global reporting initiative data - Winkler, Deborah (Washington, DC, 2017)
"This paper examines the role of multinational enterprises in sustainability reporting. The study assesses how multinational enterprise status correlates with a company's average disclosure rate and probability of reporting on economic, labor and social, environmental, and governance indicators. It uses a unique data set that offers company-level information on sustainability reporting from the Global Reporting Initiative, which covers 2,020 companies in 81 countries and 54 sustainability indicators. The summary statistics show that multinational enterprises and large domestic companies have higher average disclosure rates than small and medium-size enterprises. However, the econometric analysis suggests that multinational enterprise status does not matter for the average disclosure rate, but company size shows a strongly positive correlation. Differentiating by type of multinational enterprise reveals that the relationship becomes positive and significant for private companies. By contrast, the correlation between multinational enterprise status and the average disclosure rate does not vary by listing status, sector, region, or income level. Focusing on the relationship by development category also shows no significant correlation. Finally, accounting for the heterogeneity of the sustainability indicators, the study analyzes the relationship between multinational enterprise status and the probability of disclosure at the detailed indicator level, and confirms a significant correlation for 12 indicators."